2009
DOI: 10.1038/hr.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central blood pressure and cardio-ankle vascular index for association with cardiac function in treated hypertensive patients

Abstract: Recent automated applanation tonometry can measure radial pulse wave-derived central blood pressure (CBP), which has shown a prognostic value independently of peripheral blood pressure. However, CBP's clinical significance has not been fully established. We examined the associations between CBP and cardiac structure and function by comparing them with those of arterial stiffness assessed by cardio-ankle vascular index (CAVI) in treated hypertensive patients. Enrolled in the study were 102 patients (71 ± 7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…18,19 Furthermore, CAVI was not associated with the peak creatine kinase level in ACS patients. These results may suggest that CAVI would not be directly affected by the myocardial infarct size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Furthermore, CAVI was not associated with the peak creatine kinase level in ACS patients. These results may suggest that CAVI would not be directly affected by the myocardial infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 LV diastolic dysfunction is associated with an increased CAVI. 7,[17][18][19] Thus, the ACS patients, who would have an abrupt and severe myocardial ischemia, could have a higher CAVI than SAP patients. (2) Systemic acute inflammation and an elevated level of interleukin-18 are strongly associated with increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…8 PWV was significantly associated with LVMI in women but not in men. The higher prevalence of men (62%) in the study by Masugata et al 1 Although the authors did not discuss it much, the interaction between the heart and the arterial system, ventricular-arterial coupling, can be a key determinant of cardiovascular performance. Thus, the pathophysiological and clinical implications of arterial stiffness should be considered in conjunction with cardiac function.…”
mentioning
confidence: 91%
“…Elevated aortic SBP combined with a relative reduction in coronary perfusion during diastole could promote LV concentric remodeling and hypertrophy. Although arterial stiffness is one of the underlying mechanisms of increased central SBP, Masugata et al 1 found that CAVI, an index of arterial stiffness, was not related to LVMI after correcting for other confounding parameters. As central BP is influenced by other factors related to wave reflections, such as sex, heart rate and body height, central BP and arterial stiffness require different indices.…”
mentioning
confidence: 99%
See 1 more Smart Citation